PENENTUAN PORTOFOLIO OPTIMAL DENGAN METODE MULTI INDEX MODEL DAN PENGUKURAN RISIKO DENGAN EXPECTED SHORTFALL (Studi Kasus: Kelompok Saham LQ45 Periode Januari 2017 - Desember 2021) - Wanda Zulfa Fauziah; Tatik Widiharih; Di Asih I Maruddani (Jurnal Gaussian, 2023)
Various methods have been applied to determine the optimal portfolio, one of which is Multi Index Model. MIM is a method that uses more than one factors that affects stock price movements, this study uses ICI and exchange rate factors. Risk measurement is very important in financial analysis because almost all of them contain elements of risk. One form of risk measure that’s relatively popular in financial risk analysis is Value at Risk. VaR has a disadvantage because it only measures the percentile of the loss distribution without considering losses that exceed VaR and VaR isn’t coherent (it doesn’t fulfill the property of subadditivity). The risk measure used to overcome the weakness of VaR is Expected Shortfall. The results of the study using MIM method obtained the optimal portfolio consisting of BBRI (45.777%), PTPP (2.952%), and UNTR (51.271%) which provide a profit rate of 0.383%. The calculation results show that with a 95% confidence level, ES and VaR values obtained are 26.639% and 11.210%, respectively. ES value will be more precise in the context of a portfolio so that the maximum loss that will be received by the optimal portfolio investor that has been formed one month ahead is 26.639%.